The Effectiveness of Warm Compress Against Primary Dysmenorrhea Pain - Fauzia Riska Saputri; Shafira Dilla Setya Ardana; Devi Rifqi Ayuningtias; Hendi Saputra; Fathul Wahid Ilmuddin; Arif Pristianto; Tiara Fatmarizka (Prosiding University Research Colloquium, 2022)
One of the sign of puberty in woman is getting menstruation which when that condition having disorder or pathology, can cause dysmenorhea. Dysmenorrhea is sorennes in sttomach that that spread to the thigh, cramp, and low back pain that happen beore and during menstruation. Dysmenorrhea divided by two, the irst is primer dysmenorrhea (without anotomical abnormalities) and the second is scondary dysmenorrhea (with anotomical abnormalities). The impact of dysmenorrhea that happened to the 3rd semester female physiotherapy student can cause redue of study concentration result or 3rd semester physiotherapy student Muhammadiyah University of Surakarta there is 36 student that experience dysmenorrhea. Physiotherapy modality like hydrotherapy known to be able to reduce the complaint of dysmenorrhea.the purpose of this research is to known the efect of warm compress to decrease the intensity of dysmenorrhea on 3rd semester female physiotherapy student of Muhammadiyah University of Surakarta. This research design is quasi-experiment with design one-group pre-post testdesign. The number o samples used is 36 respondents. The tools used is wong baker ace pain rating scale to known the ppain intensity. The result is that there is an effect of warm compress that has been given to 3rd semester female student has shown decrease in pain intensity of dysmenorrhea.